2006
DOI: 10.1002/jmor.10438
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomical study of internal brooding in three anascan bryozoans (Cheilostomata) and its taxonomic and evolutionary implications

Abstract: The anatomical structure of internal sacs for embryonic incubation was studied using SEM and light microscopy in three cheilostome bryozoans-Nematoflustra flagellata (Waters,1904), Gontarella sp., and Biflustra perfragilis MacGillivray, 1881. In all these species the brood sac is located in the distal half of the maternal (egg-producing) autozooid, being a conspicuous invagination of the body wall. It consists of the main chamber and a passage (neck) to the outside that opens independently of the introvert. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…These similarities, along with the simple zooidal morphology and encrusting growth form of Gontarella, suggest that Gontarella might belong in the Calloporidae rather than in the Flustridae as Ostrovsky et al (2006) previously suggested. This is supported by the observation (Ostrovsky et al, 2006) that the internal brood sacs of Cauloramphus and Gontarella differ from those in representative species of the flustrid genera Nematoflustra and Biflustra, which have a different muscle arrangement and a shorter neck. In Gontarella, there is no trace of a kenozooidal ooecium, nor of a vestigial sclerite of the ooecial vescicle.…”
Section: Evolution Of Internal Brooding In Calloporidaesupporting
confidence: 68%
See 4 more Smart Citations
“…These similarities, along with the simple zooidal morphology and encrusting growth form of Gontarella, suggest that Gontarella might belong in the Calloporidae rather than in the Flustridae as Ostrovsky et al (2006) previously suggested. This is supported by the observation (Ostrovsky et al, 2006) that the internal brood sacs of Cauloramphus and Gontarella differ from those in representative species of the flustrid genera Nematoflustra and Biflustra, which have a different muscle arrangement and a shorter neck. In Gontarella, there is no trace of a kenozooidal ooecium, nor of a vestigial sclerite of the ooecial vescicle.…”
Section: Evolution Of Internal Brooding In Calloporidaesupporting
confidence: 68%
“…The internal brood sac in the genus Gontarella (Grischenko et al, 2002;Ostrovsky et al, 2006) is quite similar to that in Cauloramphus, in terms of the structure of the sac, the positions of its attached muscle bands, and the long neck. These similarities, along with the simple zooidal morphology and encrusting growth form of Gontarella, suggest that Gontarella might belong in the Calloporidae rather than in the Flustridae as Ostrovsky et al (2006) previously suggested.…”
Section: Evolution Of Internal Brooding In Calloporidaementioning
confidence: 95%
See 3 more Smart Citations